Balancing digital information-sharing and patient privacy when engaging families in the intensive care unit. (16th March 2016) - Brown, Samuel M; Aboumatar, Hanan J; Francis, Leslie; Halamka, John; Rozenblum, Ronen; Rubin, Eileen; Sarnoff Lee, Barbara; Sugarman, Jeremy; Turner, Kathleen; Vorwaller, Micah; Frosch, Dominick L
Abstract : Patients in intensive care units (ICUs) may lack decisional capacity and may depend on proxy decision makers (PDMs) to make medical decisions on their behalf. High-quality information-sharing with PDMs, including through such means as health information technology, could improve communication and decision making and could potentially minimize the psychological consequences of an ICU stay for both patients and their family members. However, alongside these anticipated benefits of information-sharing are risks of unwanted disclosure of sensitive information. Approaches to identifying the optimal balance between access to digital health information to facilitate engagement and protecting patient privacy are urgently needed. We identified eight themes that should be considered in balancing health information access and patient privacy: 1) potential benefits to patients from PDM data access; 2) potential harms to patients from such access; 3) the moral status of families within the patient-clinician relationship; 4) the scope of relevant information provided to PDMs; 5) issues around defining PDMs' authority; 6) methods for eliciting and documenting patient preferences about their family's information access; 7) the relevance of methods for ascertaining the identity of PDMs; and 8) the obligations of hospitals to prevent privacy breaches by PDMs. We conclude that PDMs should typically have access to health information from the current episode of care when the patient is decisionally impaired, unless the patient has previously expressed a clear preference that PDMs not have such access.